Respostas

2014-04-19T13:19:42-03:00
A) 5√12 + 4√24=
5√2² . 3  + 4√2² . 2 . 3=
5 . 2√3 + 4 . 2√2 . 3=
10√3 + 8√6

b)12√9 ÷ 3√3=
  12 . 3 ÷ 3√3=
   36 ÷ 3√3
2014-04-19T13:49:36-03:00
√a) 5√12+4√24
 5√12      12 | 2                                4√24     24| 2                              
                 6 | 2                                             12| 2
                 3 | 3                                               6| 2
                    1                                                 3| 3       4√24= 4√2.2.2.3= 4√2².2.3 =
                                                                         1         4√24 =4.2√6  = 8√6
  5√12 = 5√2.2.3  =5√2².3= 5.2√3=10√3

         5√12+4√24= 10√3 + 8√6 


  b) 12√9 : 3√3
   12√9         9| 3
                    3| 3
                     1           12√9 = 12√3² = 12 . 3  =36 

12√9 : 3√3 =

  12√9           36            12             12 (√3)           12√3          12√3
---------- =  --------   =   -------  =     -------------   =    ---------   =    --------- =   + 4√3  
  3√3           3√3             √3            √3(√3)             ( √3)²            3